67‐2: Invited Paper: Ambient Processing of Quantum Dot Photoresist for Emissive Displays. Issue 1 (2nd June 2017) - Lee, Ernie; Kan, Shihai; Hotz, Charlie; Yurek, Jeff; Luo, ZhongSheng; Kim, Heejae; Yamanaga, Jay; Carpenter, Amanda
Abstract : Moving the light conversion by quantum dots (QDs) from the backlight to the front of the LCD has the potential to further improve both the overall efficiency and color gamut of the display. In order to accomplish this change of architecture, the QDs have to be patterned at the sub‐pixel pitch of the display. This requires the QDs to be integrated into a photoresist at high concentration in order to produce pixels of the required size and optical density. Here we report on our fabrication and characterization of red and green QD photoresist, as well as how we model its performance in displays.